The world of the pharaohs - Baumann, Hans, 1914-1988, (Pantheon Books, 1960)
The story of a thirteen-year-old Egyptian boy's interest in his father's work as an archeologist is the vehicle for this history of Egyptian civilization and survey of the remarkable antiquities found in the Nile Valley during the past century.